AL-QUR’AN SEBAGAI PARAMETER KEBENARAN ILMU PENGETAHUAN (SAINS): KAJIAN TEORI RELIGIUSISME - Poppy Rachman (Al-Fikru : Jurnal Pendidikan Dan Sains, 2020)
Philosophy and Science are two words that are related substantially or historically. The birth of a science cannot be separated from the role of philosophy, on the contrary the development of science strengthens the existence of philosophy. Science is the largest component taught in all strata of education. Although years of studying science, scientific knowledge is not used as a reference in everyday life. Thinking is a human activity to find the truth. What is called true by someone is not necessarily true for others. Therefore we need a standard or truth criteria. One of the benchmarks of truth is to use a theory of Divine or religious truth. Natural phenomena do not stand without their relation and relevance to divine power. The nature of science in the Koran is a series of human activities with scientific procedures through observation, reasoning and intuition and contain values ​​of logic, aesthetics, wisdom, mercy and guidance for human life both in the world and in the future. The Koran contains many empirical values ​​and cues that are given knowledge both through written verses namely the Koran, as well as verses that are widely spread throughout the universe and their contents. Keywords: al-Qur'an, science, truth,